PENGARUH VOLATILITAS PENJUALAN dan KINERJA LABA TER-HADAP INFORMASI ASIMETRI DENGAN KUALITAS PELAPORAN KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ 45 - Martha, Nessi Felicia; Handoko, Jesica; Harimurti, Yohanes (Widya Mandala Surabaya Catholic University, 2015)
The financial statements are required for internal and external interests, especially for investors and creditors. The parties need some information about the company as well as information liaison between the two. In practice, it still happens of information asymetry, thats means imbalance of information between managers as information providers and investors as users of infor-mation. The cause of the asymmetry information is affected by some factors , one of the factors that lead to information asymmetry is the volatility of sales and profit performance. Information asymmetry will affect the decision making and operational market. Therefore, it required an effort to overcome the information asymmetry. The quality of financial reporting quality reduces infor-mation asymmetry. This study aimed to examine the effect of the volatility of sales and profit performance of the information asym-metry through financial reporting. The dependent variable of this study is asymmetry information, the independent variables of this study is the volatility of sales and profit performance and also there intervenes variable is the quality of financial reporting. This study took a sample of manufacturing companies listed on the Stock Exchange in LQ 45. Analysis in this study using path analysis. The results of this study indicate that the volatility of sales is not significant but has a positive direction to the infor-mation asymmetry through the quality of financial reporting and the pofit performence is not significant but has a negative direc-tion of the asymmetry of information through the quality of financial reporting.